Between the sheets : the literary liaisons of nine 20th-century women writers - McDowell, Lesley (Overlook Press, 2010)
Why did a gifted writer like Sylvia Plath stumble into a marriage that drove her to suicide? Why did Hilda Doolittle want to marry Ezra Pound when she was attracted to women? Why did Simone DeBeauvoir pimp for Jean-Paul Sartre? The list of the damages done in each of these sexual relationships between female writers and their male literary partners is long, but each relationship provokes the same question: would these women have become the writers they became without the experience of their own particular literary relationships? Focusing on the diaries, letters, and journals of each woman, this work explores nine famous literary liaisons of the twentieth century. The author examines the extent to which each woman was prepared to put artistic ambition before personal happiness, and how dependent on their male writing partners these women felt themselves to be. She probes the consequences of the women's codependence and reveals how in many instances, their partnerships liberated unspoken desires, encouraged artistic innovations, and even shored up literary reputations. Fascinating and innovative, this book is an invaluable addition to libraries of literary criticism and feminism.